Supplementation with Potato Protein Concentrate and Saccharomyces boulardii to an Antibiotic-Free Diet Improves Intestinal Health in Weaned Piglets - Tércia Cesária Reis de Souza; Gerardo Mariscal Landín; Ulisses Moreno Celis; Teresita Hijuitl Valeriano; José Guadalupe Gómez-Soto; Christian Narváez Briones (Animals)
Many countries have banned the use of antibiotics in livestock feed due to the development of antibiotic-resistant bacteria. Therefore, it is necessary to identify suitable alternatives to antibiotics in order to maintain intestinal health and improve piglet performance after weaning. The objective of this study was to evaluate how the intake of two functional foods—potato protein concentrate (PP) and Saccharomyces boulardii (Sb), either isolated or combined—would affect productive performance and some digestive morphophysiological responses after two weeks post-weaning. We evaluated five diets: SB, with Sb; PPC, with PP; PPC-SB, with a combination of PP and Sb; C−, without antibiotics, Sb, or PP; and C+, with antibiotics. Neither the absence of antibiotics in the diet nor the inclusion of PP and Sb affected performance or digestive organ development during the post-weaning phase. Piglets fed the C+ diet and the PP-Sb combination had higher concentrations of occludin proteins and longer villi in the jejunum compared to those fed C−, PPC, and SB. The use of Sb alone or in combination with PP increased fecal Lactobacillus, while antibiotics reduced coliform bacteria. The PP-Sb combination prevented the atrophy of the jejunal villi and promoted adhesion between enterocytes in the jejunum. Including these functional foods in piglet diets contributed to maintaining intestinal health during the critical post-weaning phase. However, further research is needed to validate and enhance the conclusions of this study.